Pentylenetetrazol-induced seizures in rats: an ontogenetic study - Velisek, L; Kubova, H; Pohl, M; Stankova, L; Mares, P; Schickerova, R (Naunyn-Schmiedeberg's archives of pharmacology, 1992)
A quantitative description of motor seizures induced by pentylenetetrazol (PTZ, metrazol) was performed. Seizures were induced by PTZ in doses from 40 to 120 mg/kg s.c. in 477 male albino rats of the Wistar strain 7 to 90 days old. Two patterns of seizures were elicited: minimal, i.e. predominantly clonic seizures of facial and forelimb muscles with preserved righting ability, and major, i.e. generalized tonic-clonic seizures with a loss of righting reflex. Minimal seizures could be reliably elicited since the age of 18 days; the CD50 for these seizures did not significantly differ with age. Major seizures were elicited regularly at all developmental stages studied. Their CD50 did not significantly differ among 7-, 12- and 25-day-old rat pups but the value for 18-day-old rats was smaller and for adult animals larger than these three age groups.
Keywords: Pentylenetetrazole; Animals; vztah mezi dávkou a účinkem léčiva; Rats, Wistar; Seizures; epilepsie tonicko-klonická; Aging; pentylentetrazol; injekce subkutánní; Dose-Response Relationship, Drug; Male; Injections, Subcutaneous; stárnutí; Epilepsy, Tonic-Clonic; krysa rodu Rattus; zvířata; mužské pohlaví; Rats; záchvaty; potkani Wistar